PenKid measurement at admission is associated with outcome in severely ill burn patients. Issue 6 (September 2020) - Dépret, François; Polina, Adrien; Amzallag, Juliette; Fayolle-Pivot, Laure; Coutrot, Maxime; Chaussard, Maïté; Struck, Joachim; Hartmann, Oliver; Jully, Marion; Fratani, Alexandre; Oueslati, Haikel; Cupaciu, Alexandru; et al.
Highlights: PenKid at admission (penKidadmin ) is the first plasmatic dosage of penKid at admission. PenKidadmin is associated with risk of AKI and mortality in burn patients. PenKidadmin adds value on top of serum creatinine and SOFA to predict mortality. PenKidadmin did not add value to Screatadmin to predict AKI. Sub-AKI detected with penKidadmin is associated with an increased risk of death. Abstract: Background: Proenkephalin A 119–159 (penKid) has been proposed as a sensitive biomarker of renal function. This study evaluated the association of concentrations of plasma penKid with death and risk of acute kidney injury (AKI) in severely ill burn patients. Methods: A prospective observational study in two centers with severely ill adult burn patients was conducted. The inclusion criteria were total body surface area (TBSA) burns >15%, with burn injury occurring <72 h before intensive care unit (ICU) admission and plasma sample taken at admission. The primary endpoint was 90-day mortality. The secondary endpoints were AKI and a combined endpoint of 90-day mortality and/or AKI. Mortality was also evaluated in the sub-group of patients with sub-clinical AKI, defined as a patient without AKI but with elevated penKid. Results: A total of 113 consecutive patients were enrolled. The median age was 48 years (Interquartile range [IQR] 33–64), the median burn TBSA was 35% (IQR 25–53), and 90-day mortality was 31.9%. Thirty-one percent of the patients had AKI, and 41.6% of patients had the combined endpoint. There was a stepwise decrease in survival from patients without AKI, sub-AKI, and with AKI (survival rate 90.0% [95% CI 82.7–97.9], 66.7% [95% CI 48.1–92.4], and 31.4% [95% CI 19.3–51.3], respectively, p < 0.001). Plasma penKid concentration was significantly higher in non-survivors compared to survivors (86.9 pmol/L [IQR 53.3–166.1] versus 52.9 pmol/L [IQR 37.1–70.7]; p = 0.0001) and in patients with AKI compared to patients without AKI (86.4 pmol/L [IQR 56.5–153.4] versus 52.5 pmol/L [IQR 35.5–71.2]; p < 0.001). Penkid provided added value on top of serum creatinine (Screat) and Sepsis Related Organ Failure Assessment (SOFA) scores to predict 90-day mortality (combined c-index of 0.738 versus 0.707; p = 0.024 and 0.787 versus 0.752; p < 0.001). Conclusions: Plasma penKid concentration at admission was associated with an increased risk of death in burn patients. PenKid has additional prognostic value on top of Screat and SOFA to predict 90-day mortality.